Association of Central Retinal Arteriolar and Venular Equivalents with Brain-aging and Macular Ganglion Cell-inner Plexiform Layer Thickness. (2nd January 2023) - Paulsen, Adam J.; Pinto, Alex A.; Merten, Natascha; Schubert, Carla R.; Chen, Yanjun; Klein, Barbara E.K.; Meuer, Stacy M.; Cruickshanks, Karen J.
ABSTRACT: Introduction: Neurodegeneration and cognitive decline in aging are growing public health concerns. This study investigates associations between central retinal arteriolar and venular equivalents (CRAE, CRVE) and brain-aging, a sensory and cognitive test composite measure, and macular ganglion cell-inner plexiform layer (mGCIPL) thickness, a biomarker of neurodegeneration. Methods: Beaver Dam Offspring Study (BOSS) participants are adult children (baseline (2005–2008) age 21–84 years) of the population-based Epidemiology of Hearing Loss Study participants. Follow-up occurred every 5 years. In 2010–2013, fundus photographs were used to measure retinal vessels. A brain-aging score was constructed by principal component analysis using sensorineural and cognitive data. Associations between incident brain-aging and vessel measures were investigated using logistic regression. Associations between CRAE and CRVE and mGCIPL thickness, measured in 2015–2017, were also investigated. Results: Participants (N = 2381; mean age: 53.9 years (SD = 9.8); 54% women) had a mean CRAE and CRVE of 148.8 µm (SD = 14.5) and 221.7 µm (SD = 20.7), respectively. Among those without ocular conditions, wider CRAE was associated with decreased 5-year brain-aging risk (33% per SD CRAE increase). Both vessel measures were independently associated with mGCIPL thickness. The mGCIPL thickness increased by approximately 1.7 µm and 2.0 µm per SD increase in CRAE and CRVE, respectively. Discussion: The association of CRAE with incident brain-aging indicates its potential use as a screening tool among those without eye disease. The associations between CRAE and CRVE and mGCIPL thickness indicate narrower vasculature could affect neuronal health. These associations point to potential usefulness of retinal vessel measurements to identify people at higher risk of sensorineural declines and neurodegeneration.